3D‐Printed Atsttrin‐Incorporated Alginate/Hydroxyapatite Scaffold Promotes Bone Defect Regeneration with TNF/TNFR Signaling Involvement. Issue 11 (17th June 2015) - Wang, Quan; Xia, Qingqing; Wu, Yan; Zhang, Xiaolei; Wen, Feiqiu; Chen, Xiaowen; Zhang, Shufang; Heng, Boon Chin; He, Yong; Ouyang, Hong‐Wei
<x xml:space="preserve">Abstract</x> High expression levels of pro‐inflammatory tumor necrosis factor (TNF)‐α within bone defects can decelerate and impair bone regeneration. However, there are few available bone scaffolds with anti‐inflammatory function. The progranulin (PGRN)‐derived engineered protein, Atsttrin, is known to exert antagonistic effects on the TNF‐α function. Hence, this study investigates whether 3D‐printed Atsttrin‐incorporated alginate(Alg)/hydroxyapatite(nHAp) scaffolds can facilitate bone healing through affecting the TNF/TNFR signaling. A 3D bioprinting system is used to fabricate Atsttrin‐Alg/nHAp composite scaffolds, and the Atsttrin release from this scaffold is characterized, followed by evaluation of its efficacy on bone regeneration both in vitro and in vivo. The 3D‐printed Atsttrin‐Alg/nHAp scaffold exhibits a precisely defined structure, can sustain Atsttrin release for at least 5 days, has negligible cytotoxicity, and supports cell adhesion. Atsttrin can also attenuate the suppressive effects of TNF‐α on BMP‐2‐induced osteoblastic differentiation in vitro. The 3D‐printed Atsttrin‐Alg/nHAp scaffold significantly reduces the number of TNF‐α positive cells within wound sites, 7 days after post‐calvarial defect surgery. Additionally, histological staining and X‐ray scanning results also show that the 3D‐printed Atsttrin‐Alg/nHAp scaffold enhances the regeneration of mice calvarial bone defects. These findings thus demonstrate that the precise structure and anti‐inflammatory properties of 3D‐printed Atsttrin‐Alg/nHAp scaffolds may promote bone defect repair.